Local influence in the dimensions of designing birthing spaces for the Malay-Muslim Malaysians - Mohd Nawawi, Norwina (2006)
Aims and Objectives: The study aims to uncover the myth and realities of cultural and belief influence in the design of preferred birthing spaces for the selected Malay-Muslim population of Malaysia and compare them to the clinical settings of existing community based maternity units with the objective of finding a conducive design for better health outcome for mother and child. The study aim to dispel the notion of universal birthing space for all localities and that architects should consider the cultural and spiritual dimension in each of their design for better outcome.